Human mobility variations in response to restriction policies during the COVID-19 pandemic: An analysis from the Virus Watch community cohort in England, UK - Cheng, Tao; Chen, Tongxin; Liu, Yunzhe; Aldridge, Robert W.; Nguyen, Vincent; Hayward, Andrew C.; Michie, Susan (Frontiers in Public Health, 2022)
Objective: Since the outbreak of COVID-19, public health and social measures to contain its transmission (e.g., social distancing and lockdowns) have dramatically changed peopleâs lives in rural and urban areas globally. To facilitate future management of the pandemic, it is important to understand how different socio-demographic groups adhere to such demands. This study aims to evaluate the influences of restriction policies on human mobility variations associated with socio-demographic groups in England, UK. Methods: Using mobile phone global positioning system (GPS) trajectory data, we measured variations in human mobility across socio-demographic groups during different restriction periods from Oct 14, 2020 to Sep 15, 2021. The six restriction periods which varied in degree of mobility restriction policies, denoted as `Three-tier Restriction', `Second National Lockdown', `Four-tier Restriction', `Third National Lockdown', `Steps out of Lockdown', and `Post-restriction', respectively. Individual human mobility was measured with respect to the time period people stayed at home, visited places outside the home, and travelled long distances. We compared these indicators across the six restriction periods and across socio-demographic groups. Results: All human mobility indicators significantly differed across the six restriction periods, and the influences of restriction policies on individual mobility behaviours are correlated with socio-demographic groups. In particular, influences relating to mobility behaviours are stronger in younger and low-income groups in the second and third national lockdowns. Conclusions: This study enhances our understanding of the influences of COVID-19 pandemic restriction policies on human mobility behaviours within different social groups in England. The findings can be usefully extended to support policy-making by investigating human mobility and differences in policy effects across not only age and income groups, but also across geographical regions.